Spontaneous Crack Healing in Nanostructured Silica-Based Thin Films - Itoh, Shun; Kodama, Satoshi; Kobayashi, Maho; Hara, Shintaro; Wada, Hiroaki; Kuroda, Kazuyuki; Shimojima, Atsushi (ACS nano, 2017)
Self-healing materials that can spontaneously repair damage under mild conditions are desirable in many applications. Significant progress has recently been made in the design of polymer materials capable of healing cracks at the molecular scale using reversible bonds; however, such a self-healing mechanism has rarely been applied to rigid inorganic materials. Here, we demonstrate the self-healing ability of lamellar silica-based thin films formed by self-assembly of silica precursors and quaternary ammonium-type surfactants. Specifically, spontaneous healing of cracks (typically less than 1.5 μm in width) was achieved under humid conditions even at room temperature. The randomly oriented lamellar structure with thin silica layers is suggested to play an essential role in crack closure and the reformation of siloxane networks on the fracture surface. These findings will lead to the creation of smart self-healing silica-based materials based on reversible siloxane bonds.